Correspondencia diagnóstica entre criterios NICE vs AAP en hiperbilirrubinemia de neonatos de 35 - 36 semanas. Riobamba, 2019 - Karina Michelle, Tricerri Moya (2020)
The present investigation is based on the study to identify the best diagnostic criteria for the detection of neonatal hyperbilirubinemia according to those proposed by the National Institute of Health and Clinical Excellence of the United Kingdom (NICE) and the American Academy of Pediatrics (AAP), in premature newborns aged 35 to 36 weeks at the General Hospital of the Ecuadorian Social Security Institute (IESS) in the city of Riobamba in the period 2017-2019. In the application of the scientific method, the research problem, the methodology, the results and their discussion were identified. Chapter one responds to the identification of the problem, the general objective and the specific objectives. Chapter two responds to the bibliographic review that supports this research. Chapter three responds to the design of the methodology used, the focus of this research being of a mixed type, based on a documentary review, with a study population of 42 preterm newborns aged 35 to 36 weeks, with the same number of units study. Chapter four responded to the results of the research with the help of the SPSS system, the univariate, bivariate and multivariate analysis, the ROC analysis, and the hypothesis was tested through the Chi Square system and; finally the discussion of the results, conclusions and recommendations.